BS ISO/IEC 30105-8. Information technology. IT Enabled Services-Business Process Outsourcing (ITES-BPO) lifecycle processes. Part 8. Continual Performance Improvement (CPI) of ITES-BPO (18th January 2022) - British Standards Institution,
No abstract available